2018
DOI: 10.3389/fmicb.2018.01492
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure and Functional Potential Along a Hypersaline Gradient

Abstract: Salinity is one of the strongest environmental drivers of microbial evolution and community composition. Here we aimed to determine the impact of salt concentrations (2.5, 7.5, and 33.2%) on the microbial community structure of reclaimed saltern ponds near San Francisco, California, and to discover prospective enzymes with potential biotechnological applications. Community compositions were determined by 16S rRNA amplicon sequencing revealing both higher richness and evenness in the pond sediments compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 83 publications
4
38
0
Order By: Relevance
“…In general, sediments exhibited a greater diversity in terms of OTU to sequence ratio compared to brine. This is in support of the view that sediments support a broad range of microorganisms because of the availability of a wide range of organic nutrients and hypersaline soils are no exception to this pattern (Sander and Kalff, 1993;Kimbrel et al, 2018). Though the statistical analysis indicated that the taxonomic composition between the brine and sediments during different salt production phases are similar, we acknowledge the low statistical power involved in the analysis due to the composite sampling approach resulting in single sample per sampling location.…”
Section: Coastal Salterns Of Siridao Are One Of the Most Diverse Solasupporting
confidence: 77%
See 2 more Smart Citations
“…In general, sediments exhibited a greater diversity in terms of OTU to sequence ratio compared to brine. This is in support of the view that sediments support a broad range of microorganisms because of the availability of a wide range of organic nutrients and hypersaline soils are no exception to this pattern (Sander and Kalff, 1993;Kimbrel et al, 2018). Though the statistical analysis indicated that the taxonomic composition between the brine and sediments during different salt production phases are similar, we acknowledge the low statistical power involved in the analysis due to the composite sampling approach resulting in single sample per sampling location.…”
Section: Coastal Salterns Of Siridao Are One Of the Most Diverse Solasupporting
confidence: 77%
“…Though the occurrence of halophilic archaea in the low salinity environments has been documented before, the large number of sequences observed in the salterns of Siridao is unprecedented. Recently, Kimbrel et al (2018) have shown that at 7.5% salinity, there were about 20% and 18% of archaeal sequences in brine and sediments obtained from a solar saltern respectively. Similarly, Elshahed et al (2004) have reported the isolation of halophilic archaeal clones belonging to Halogeometricum, Natronomonas, Halococcus, and Haloferax from low salinity (0.7 -1%) brine and sediment samples.…”
Section: Archaea Dominates the Low And Moderate Salinity Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…depositum Y78, is flanked by two annotated tRNA-thr genes (FGM06_RS03355 and FGM06_RS03870), and has an integrase gene close to one end (FGM06_RS03360). The second provirus we designated ELPmg-prov1, and was described as part of a metagenomic study of the Eden Landing Ponds, San Francisco, USA [19]. It is 77.7 kb long, has an integrase gene near one end, and has recombined into a tRNA-Thr gene present on an 82.4 kb contig.…”
Section: Hf1-group Provirusesmentioning
confidence: 99%
“…Eiler et al (2014) characterized microbial communities using metagenomic data for various freshwater samples (lakes in the USA and Sweden) and marine locations. For hypersaline settings, we used metagenomic data from the Santa Pola salterns in Spain (Ghai et al, 2011;Fernandez et al, 2013), natural soda lakes of the Kulunda Steppe in Serbia (Vavourakis et al, 2016), and South Bay salterns in California, USA (Kimbrel et al, 2018). The compositional analysis reveals a relatively low n H2O of proteins inferred from the marine metagenomes compared to freshwater samples in the Eiler et al dataset (Fig.…”
Section: Compositional Trends In Rivers Lakes and Hypersaline Envirmentioning
confidence: 99%